A Contemporary View on Online and Web Tools for Students with Sensory & Learning Disabilities - Bravou, Vasiliki; Drigas, Athanasios S. (International Journal of Online and Biomedical Engineering (iJOE), 2019)
In the last 30 years, the use of information and communication technologies, the evolution of hardware and software for special needs people, as well as the spreading of the World Wide Web, is assisting people with disabilities in overcoming obstacles, accessing information, learning and participating in activities, which otherwise were not able to carry out. Special needs education is the process adjusting the education of learners with disabilities according to their unique requirements. Evolvement of technology has made computers and mobile devices capable of complementing usual teaching processes for students with special needs. In this report we present a summary of some representative online applications for assisting disabled people in the learning process and their daily lives.